Comprehensive neurosurgery board review - Citow, Jonathan Stuart (Thieme, 2020)
The quintessential neurosurgical text review for acing the ABNS written exam! Since its publication nearly 20 years ago, Comprehensive Neurosurgery Board Review has garnered legendary status as the leading high-yield review for neurosurgical residents preparing for the American Board of Neurological Surgery (ABNS) primary exam. The updated third edition by Jonathan S. Citow and associate editors R. Loch Macdonald, Ross C. Puffer, Syed I. Khalid, Bob S. Carter, Alan R. Cohen, Robert J. Spinner, and Daniel Refai reflects technological advances made in the past decade.